Serum Leptin levels in Obese Post MenopauseWomen - Al-Zubaidy A. Ghaith; Fadhil A. Khazraj (College of Pharmacy / Mustansiriyah University, 2009)
The objective of this study is to find the relationship between leptin and obesity in post menopause women. Serum leptin level was determined by using the Enzyme Linked Immuno Sorbant Assay (ELISA) technique, The Body Mass Index (BMI) was measured by weight (kg)/square height (m²), and waist circumference was measured in centimeters. These parameters where taken from 100 post menopause women who were divided according to BMI into two groups: 60 obese women and 40 nonobese women. A highly significant difference in Serum Leptin levels, BMI and Waist circumference was found in the obese post menopause women compared with non-obese subjects (p≤0.01). And a highly significant positive correlation between serum leptin levels and BMI (r=0.739, p≤0.01), and between serum leptin levels and waist circumference (r=0.684, p≤0.01).